The Representation of Childhood in Roald Dahl’s The Big Friendly Giant - Daempal, Anggun Ester; Mamentu, Agustin C.; Sabudu, Delli (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This study explores the representation of childhood in Roald Dahl's "The Big Friendly Giant" through the lens of Erik Erikson's psychosocial development theory, with a particular focus on the character of Sophie, an orphan who faces significant challenges. The research aims to analyze how Sophie's journey reflects key developmental stages, including trust vs. mistrust, autonomy vs. shame and doubt, initiative vs. guilt, and industry vs. inferiority. Through her evolving relationship with the BFG and her proactive role in confronting the giants, Sophie transitions from a fearful, passive child to a confident, assertive individual. This transformation illustrates a positive representation of childhood, emphasizing the importance of nurturing environments and supportive relationships in child development. The findings highlight the critical role of literature in shaping societal perceptions of childhood and suggest that narratives like Dahl's can foster resilience and self-assurance in children. This study also underscores how Sophie's resilience embodies hope, courage, and adaptability, which are vital for healthy psychosocial development.